2016
DOI: 10.1099/jgv.0.000315
|View full text |Cite
|
Sign up to set email alerts
|

Serological and viraemic status of human cytomegalovirus infection in patients with colorectal cancer is not correlated with viral replication and transcription in tumours

Abstract: Colorectal cancer (CRC) is amongst the leading causes of cancer-related mortality worldwide. Emerging evidence suggests that human cytomegalovirus (HCMV) exists in the tumour tissue of CRC and is associated with disease outcome. To study whether tumoral HCMV is related to viral reactivation in blood, tumour specimens and pre-and post-operative blood samples from CRC patients were collected prospectively. PCR and quantitative PCR were performed to detect HCMV DNA. HCMV IgG and IgM antibodies were measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…We found that there was a certain prevalence of HCMV DNA (28.7%) in CRC tissues, compared to a high rate of HCMV detection (over 80%) in patients’ plasma [16, 21]. Some reports attributed low or negative detection to the type of sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that there was a certain prevalence of HCMV DNA (28.7%) in CRC tissues, compared to a high rate of HCMV detection (over 80%) in patients’ plasma [16, 21]. Some reports attributed low or negative detection to the type of sample.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate data has been obtained to confirm the causal role of HCMV in carcinogenesis processes, tumor progression and metastasis [19]. Although HCMV infection is considered to have relationship with CRC, the clinical and pathological features of patients are also various [20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…Its sensitivity was better than that for detecting HCMV US28 gene (S1 Table). Our colleagues from our department had detected HCMV UL73 gene in 42.2% (35/83) of the colorectal tumor samples [36] and shown good correlation with the result of PCR for HCMV UL55 in 23 pairs of colorectal cancer and adjacent non-neoplastic specimen [33]. In regard to the age of the specimen, Ranganathan et al had demonstrated that detecting HCMV UL144 gene in GBMs was more sensitive than detecting UL28 and UL55, especially for older formalin-fixed, paraffin-embedded (FFPE) samples [37].…”
Section: Discussionmentioning
confidence: 99%
“…Whether such Based on the results of this study and our previous work that compared the viral loads in tumour and normal specimens of CRC (Chen et al, 2012), we speculate that HCMV directly infects, or reactivates within, the neoplastic epithelium of CRC. Virus replication possibly correlated with changes in the tumour microenvironment, since the serologic and viraemic status of HCMV is not associated with viral replication and transcription in tumour tissues (Chen et al, 2016). Furthermore, since the ISH probe targeted the most abundantly transcribed viral gene during permissive infection (McSharry et al, 2003;Wu et al, 1992), the virus is probably not 'dormant' in tumours of CRC.…”
Section: Discussionmentioning
confidence: 99%